Technology and Law Enforcement: The Transformation of the Calgary Police Force, 1900-1940 - Bright, David (Urban History Review / Revue d'histoire urbaine, 2005)
As was the case in cities across North America, Calgary's police force underwent a transformation in the early twentieth century. In particular, new technologies were embraced and utilized, notably in the fields of training, communication, identification, and records. Yet while this process of modernization certainly eased the day-to-day operations of Calgary's law enforcers, it provided mixed results in increasing the rate of conviction across a wide range of offences. As such, this article offers a caution against equating modernization and professionalization, per se, with improvements in effective policing.